2007
DOI: 10.3319/tao.2007.18.2.295(tcdp)
|View full text |Cite
|
Sign up to set email alerts
|

Core Slabbing and Nannofossil Analysis on the Chelungpu Fault Zone, Taichung, Taiwan

Abstract: The results of this nannofossil analysis supply essential information for determining the formation boundaries in the upper Pliocene to Pleistocene. These results also verify the existence of a repetition fossil zone.The TCDP well-A was sunk through the soft fine-grain muddy sandstone and mudstone dominated formations of the Pliocene and Pleistocene in the Taichung area. This study determines methods for providing core preservation in wells at fault zones and establishes a nannofossil biostratigraphy for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Characteristics of these sandstones are similar in lithology to surface exposed Cholan Formation. Reworked Miocene fossils and nannofossil assemblages (Wu et al 2007) also indicate that the footwall of the Sanyi fault is made up of repeated Cholan formation. Along with increasing regional bedding dip with depth, an abrupt change of physical properties occurred across FZA1710, below which values of resistivity, density and sonic velocities ( V p and V s ) are significantly reduced by 50, 3, 18 and 25 per cent, respectively.…”
Section: Subsurface Structure Physical Properties and Log Unitsmentioning
confidence: 99%
“…Characteristics of these sandstones are similar in lithology to surface exposed Cholan Formation. Reworked Miocene fossils and nannofossil assemblages (Wu et al 2007) also indicate that the footwall of the Sanyi fault is made up of repeated Cholan formation. Along with increasing regional bedding dip with depth, an abrupt change of physical properties occurred across FZA1710, below which values of resistivity, density and sonic velocities ( V p and V s ) are significantly reduced by 50, 3, 18 and 25 per cent, respectively.…”
Section: Subsurface Structure Physical Properties and Log Unitsmentioning
confidence: 99%
“…Generalized lithology of the Taiwan Chelungpu-fault Drilling Project and locations of faults. Formation boundaries are based on nannofossil assemblages (Lin et al 2007, Wu et al 2005. Locations of samples used in this study are indicated by red stars.…”
Section: Geochemical Changes In Fault Zone Rocksmentioning
confidence: 99%
“…Core observations on lithology, nannofossils, structures and well loggings indicate that the three sedimentary formations of western Taiwan can be identified: the PlioPleistocene Chulan Formation, the Pliocene Chinshui Shale, and the Miocene Kueichulin Formation. In addition, at least six major fault zones can be recognized in the cores; those at depth 1111 m (FZ1111) and 1712 m (FZ1712) may correspond to the Chelungpu and Sanyi faults, respectively Hung et al 2007;Wu et al 2007). Detailed descriptions on the meso-structures at three shallower fault zones have been given in this issue .…”
mentioning
confidence: 99%